Figurines de terre cuite et questions de muséographie - Violaine Jeammet (Les Carnets de l’ACoSt)
This article constitutes a chapter in the forthcoming Handbook for Coroplastic Research that is in preparation by an international team of researchers. 1 It details the museological approach to the study of Greek figurative terracottas, both past and present, especially as it is represented by the collection of the Louvre Museum.